Bacterial lysate treatment in allergic disease: A systematic review and meta‐analysis. Issue 8 (5th July 2021) - Li, Chengmei; Zhou, Hua; Zhang, Wei; Che, Datian
Abstract: Objective: The aim of this review was to assess the efficacy of bacterial lysate treatment in patients with allergic disease. Method: Randomized controlled trials (RCTs) of bacterial lysate therapy for patients with allergic diseases (asthma, atopic dermatitis, and allergic rhinitis) were searched using PubMed, EMBASE, Cochrane, China National Knowledge Infrastructure, Chinese Biomedical literature, and Wanfang databases up to March 2020. Based on the guidelines of the Cochrane collaboration, risk of bias was assessed. Results: This meta‐analysis based on 19 studies comparing bacterial lysate‐treated patients with a control group showed a 24% (RR: 1.24, 95% CI [1.19, 1.30]) increase in improvement of allergy symptom control. In addition, the improvement of asthma symptom control was 22% (RR: 1.22, 95% CI [1.14, 1.26]) higher in the bacterial lysate treatment group. Moreover, the levels of immunoglobulin (IgA and IgG), T lymphocyte subtype (CD3+, CD4+, CD4+/CD8+, Th1), and cytokines (IFN‐γ, IL‐2, and IL‐12) were increased in the treated group compared with controls. There was no significant difference in adverse event rate between the two groups. Conclusion: Treatment with bacterial lysate improves symptom control in patients with allergic diseases on the basis of routine therapy. No adverse risk was found in this meta‐analysis.